2023
DOI: 10.1097/md.0000000000032735
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio as markers of stable ischemic heart disease in diabetic patients: An observational study

Abstract: Ischemic heart disease (IHD) is a pressing public health concern with high prevalence, mortality, and morbidity. Although the value of neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) as markers of the acute coronary syndrome are well recognized, there is a paucity of data deciphering their role in screening for stable ischemic heart disease (SIHD) in the presence of type 2 diabetes mellitus (T2DM). The present study investigates the value of NLR and PLR as markers of SIHD in T2DM. We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Presently, IDRs are extensively utilized across a diverse spectrum of medical disciplines as a dependable and conveniently accessible metric for gauging the immune reaction to a range of both infectious and noninfectious triggers. These ratios are subject to the influences of numerous factors, encompassing variables like diabetes, obesity, psychiatric disorders, solid organ malignancies, sepsis, pharmaceutical interventions, acute and chronic vascular disease, including coronary heart disease and stroke, and viral infections such as the SARS-CoV-2 virus [21,22]. Our analysis suggests that the preoperative values of three of the IDRs-namely, NLR, SII, and PLR, respectively-are elevated in POGD patients and seem to positively correlate with the duration of intestinal paresis, as assessed by the Tf, TL, and NGtR.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, IDRs are extensively utilized across a diverse spectrum of medical disciplines as a dependable and conveniently accessible metric for gauging the immune reaction to a range of both infectious and noninfectious triggers. These ratios are subject to the influences of numerous factors, encompassing variables like diabetes, obesity, psychiatric disorders, solid organ malignancies, sepsis, pharmaceutical interventions, acute and chronic vascular disease, including coronary heart disease and stroke, and viral infections such as the SARS-CoV-2 virus [21,22]. Our analysis suggests that the preoperative values of three of the IDRs-namely, NLR, SII, and PLR, respectively-are elevated in POGD patients and seem to positively correlate with the duration of intestinal paresis, as assessed by the Tf, TL, and NGtR.…”
Section: Discussionmentioning
confidence: 99%
“…(Elsanan et al, 2023). Another study conducted by Joshi et al, (2023) also found that PLR could be a predictor of stable ischemic heart disease (SIHD) in diabetes mellitus patients with a sensitivity sensitivity of 73% and a specificity of 46% (Joshi et al, 2023).…”
Section: Plr In Diabetes Mellitus Patientsmentioning
confidence: 94%
“…The findings announced a positive pertinence between NLR and fasting blood glucose (FBG), HOMA-IR. Within T2DM, elevated levels of NLR and PLR had been found to be positively associated with microalbuminuria [ 12 ], as well as being relevant to severity of carotid plaque [ 13 ] and stable ischemic heart disease [ 14 ]. Among individuals with diabetic retinopathy (DR), there was a notable elevation in the levels of NLR, MLR and PLR in comparison to those without DR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%